PERAN KOMPENSASI DAN KARAKTERISTIK LEADERSHIP PADA KINERJA GURU YANG DIMEDIASI OLEH KEPUASAN KERJA - Ilmawan, Mirza Dwinanda; Noermijati, Noermijati (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2016)
The objective of this research is to analyze direct and indirect effects of compensation on State Senior High School (SMA) teachers’ performances in Malang City mediated by work satisfaction. This research also aims to analyze direct and indirect influence of leadership characteristics on State Senior High School (SMA) teachers’ performances in Malang City mediated by work satisfaction. The population of this research is all teachers of State Senior High School (SMA) in Malang City who have got Sertifikasi Guru amounted at 460 people and the sampling technique is Proportional Random Sampling which results sample of 100 people. The primary data collecting uses questionnaires as instrument. Data analysis method using path analysis technique. This research results indicate that compensation directly influences teacher’s performances. It also proves indirect influence of compensation on teachers’ performances mediated by work satisfaction. Other than those, it states that leadership characteristics affects on teachers’ performances directly. And leadership characteristics affects on teachers’ performances mediated by work satisfaction.